H-reflex amplitude depression as a marker of presynaptic inhibition in Painful Diabetic Neuropathy (PDN). - Ahmad Asmedi; Samekto Wibowo; Lucas Meliala (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACTPainful Diabetic Neuropathy (PDN) is a common complication of diabetes mellitus (DM). Disruption in presynaptic inhibition in dorsal horn of the spinal cord has been proposed as one of the pathomechanism of PDN. Previous research showed that presynaptic inhibition can be detected by H-reflex examination. The aim of this study was to know whether the reduction of presynaptic inhibition in spinal dorsal horn of PDN patients really exist, and detectable by H-reflex examination. It was cohort prospective involving 141 (58 men, 83 women) patients with DM and impaired glucose tolerance (IGT) between the ages of 40 and 61 years from several health facilities in Yogyakarta. All patients underwent clinical, laboratory and electrodiagnostic examination. Demographic, clinical and electrodiagnostic data were collected and analyzed. By survival analysis there were 25 new cases of PDN (12.12% cumulative incidence). Using survival Kaplan Meier analysis, the significant hazard ratio for PDN were 12.81 for median motor nerve amplitude, 5.74 for median nerve distal latency, 3.71 for median sensory nerve amplitude, 6.33 for median sensory latency, 3.4 for tibial nerve amplitude, 3.48 for tibial nerve distal latency, 2.29 for sural nerve amplitude, 4.47 for sural nerve latency, 3.99 for H-reflex latency, 5.88 for H-reflex amplitude, and 17.83 for Diabetic Neuropathy (DN) status. Using hazard proportional cox analysis, only H amplitude and DN status (DNS score) were significantly correlated with PDN (p= 0.026; hazard ratio = 15.450; CI 95%= 1.39 – 171.62 for H amplitude and p= 0.030; hazard ratio = 10.766; CI 95%=1.26 – 92.09 for DN status). This study showed that depression of H-reflex amplitude was correlated with the occurrence of PDN. This result proves that there was presynaptic inhibition process in PDN that manifests as low H-reflex amplitude.